Scribal Practices in Arabic Manuscripts from Ethiopia: The ʿAjamization of Scribal Practices in Fuṣḥā and ʿAjamī Manuscripts from Harar - Fani, Sara (Islamic Africa, 2017)
This paper focuses on Arabic scribal practices in a corpus of Ethiopian Islamic manuscripts from the region of Harar ascribed to the period from the eighteenth to the early nineteenth century. Two different aspects will be considered, namely the characteristic realization of specific graphemes and the methods for the justification of the text. The observations take into account the perceived sacred dimension of the texts, from copies of the Qurʾān to ʿAjamī works, and the different level of standardization of their written manifestations. This approach is intended to highlight the results of the cultural interplay between the scribal models acquired and their local reinterpretation in order to identify reference models and determine the criteria at the base of the processes of ʿAjamization of these scribal practices. I hope that the characteristics described in this article will represent the starting point for comparative studies of scribal practices between different Ethiopian regions and with other regions of the Islamic world.